Risk Factors of Stunting in Posyandu Serasih Puskesmas Ciptodadi Musi Rawas - Susilawati, Okti; Umam, Nurcholid; Yuniasih, Dewi (Ahmad Dahlan Medical Journal, 2023)
Stunting is a growth failure in children caused by chronic malnutrition for a long time. The average prevalence of stunting in Indonesia from 2005 to 2017 was 36.4% and ranked third in Southeast Asia. The stunting prevalence in South Sumatra province reached 28.98% in 2019. The study was carried out to determine the factors influencing stunting in Serasih integrated healthcare center Ciptodadi Public Health Center Musi Rawas district. The study used a descriptive observational method with data collection through primary and secondary data. It was conducted from October to November 2021 at Serasih Integrated Healthcare Center Ciptodadi Public Health Center Musi Rawas district. The populations were toddlers in Serasih integrated healthcare center with samples of 37 stunting toddlers meeting the inclusion criteria. The analysis used was univariate and presented a frequency distribution table.  From the entire population, 40.2% of toddlers suffered from stunting with males (75,7%) and females (24,3%). In addition, stunting toddlers owned a normal birth weight (91.9%) and the highest education level of mothers was senior high school (64.9%). Furthermore, stunting toddlers did not get exclusive breastfeeding (56.8%) as well the average of feeding pattern for stunting toddlers (91.9%). The conclusion is that the biggest factors influencing stunting were male toddlers, mothers with the highest education level of senior high school, and toddlers who did not get exclusive breastfeeding.